2004
DOI: 10.1128/aem.70.3.1658-1668.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Organization of Genes of the β-Ketoadipate Pathway in Members of the Marine Roseobacter Lineage

Abstract: Members of the Roseobacter lineage, an ecologically important marine clade within the class ␣-Proteobacteria, harbor genes for the protocatechuate branch of the ␤-ketoadipate pathway, a major catabolic route for lignin-related aromatic compounds. The genes of this pathway are typically clustered, although gene order varies among organisms. Here we characterize genes linked to pcaH and -G, which encode protocatechuate 3,4-dioxygenase, in eight closely related members of the Roseobacter lineage (pairwise 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…34 % identity to the putative ABC transporter in Clostridium perfringens SM101 (Myers et al, 2006). ORF2 showed 22 % identity to the ABC transporter protein found in Silicibacter pomeroyi DSS-3 (Buchan et al, 2004), and 25 % identity to SpaE encoded on the subtilin locus of Bacillus subtilis A1/3 (Chung & Hansen, 1992). These results suggested that bovE, bovF, ORF1 and ORF2 might form an ABC-transporter-like complex which contributes to self-protection of S. bovis HJ50 from bovicin HJ50.…”
Section: Resultsmentioning
confidence: 63%
“…34 % identity to the putative ABC transporter in Clostridium perfringens SM101 (Myers et al, 2006). ORF2 showed 22 % identity to the ABC transporter protein found in Silicibacter pomeroyi DSS-3 (Buchan et al, 2004), and 25 % identity to SpaE encoded on the subtilin locus of Bacillus subtilis A1/3 (Chung & Hansen, 1992). These results suggested that bovE, bovF, ORF1 and ORF2 might form an ABC-transporter-like complex which contributes to self-protection of S. bovis HJ50 from bovicin HJ50.…”
Section: Resultsmentioning
confidence: 63%
“…Enzymes involved in the protocatechuate branch of the ␤-ketoadipate pathway in S. meliloti are encoded within the pcaDCHGB and pcaIJF operons, which are subject to regulation by products encoded by pcaQ and pcaR, respectively (23). The regulator encoded by pcaQ is a member of the LysR-type transcriptional regulator (LTTR) superfamily, and PcaQ homologues are present in many species of ␣-proteobacteria (3,4,7,23,34,36,37).LysR-type regulators comprise one of the largest groups of prokaryotic transcriptional regulators characterized to date; these proteins regulate a diverse range of regulons, including genes whose products are involved in nitrogen and carbon fixation, biofilm formation, the oxidative stress response, bacterial virulence, and the catabolism of various compounds, including aromatic acids (10,16,19,22,23,28,34,46,47,51,55,57). LTTR proteins consist of a conserved helix-turn-helix DNA binding motif located in the N-terminal portion of the polypeptide, whereas the C terminus includes an inducer binding site.…”
mentioning
confidence: 99%
“…Together with the fact that many IS-like elements and transposase genes are flanked with the pca gene cluster, it suggests that the b-ketoadipate pathway genes may be acquired via transposition events and subsequently distributed among actinobacteria via the horizontal transfer of plasmids. Eulberg et al (1998) first found a pcaL gene that encoded a merged enzyme with b-ketoadipate enol-lactone hydrolase and c-carboxymuconolactone decarboxylase in the rhodococcal pca gene cluster, although these two enzymes are encoded by separate genes, pcaD and pcaC, respectively, in most proteobacteria (Buchan et al, 2004). In addition, Iwagami et al (2000) identified the pcaL gene homologue in the streptomycete pca gene cluster (strain 2065).…”
Section: Discussionmentioning
confidence: 99%
“…1). In the case of the proteobacteria, this pathway is biochemically conserved among phylogenetically different strains, but operon organization, regulatory proteins, coinducer molecules and transport proteins for the pathway are remarkably diverse, most likely reflecting subtle aspects of niche adaptation (Buchan et al, 2004;Parke, 1997;Parke et al, 2000). In contrast, there is still little information available concerning protocatechuate catabolic gene clusters from actinobacteria (Eaton, 2001;Eulberg et al, 1998;Iwagami et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation